1938
DOI: 10.1242/jeb.15.2.225
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbon Monoxide on the Oxygen Consumption of Drosophila Melanogaster Pupae

Abstract: 1.The oxygen consumption of Drosophila melanogaster pupae during metamorphosis can be expressed by a U-shaped curve, as stated by earlier authors; that is, the consumption is high at the beginning, then falls off rapidly, and from the middle of the pupal period onwards it rises again till about the original level. 2. The oxygen consumption is strongly inhibited by carbon monoxide in all pupal stages. The inhibition is proportional to the percentage of CO and O2 in the gas mixtures and can be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

1940
1940
1972
1972

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…Bodine and Boell (1934) obtained CO-stimulation of respiration of diapause embryos of the grasshopper Mclanoplus differentialis and no significant effect of light. A similar stimulation by CO was found by Wolsky (1941) in a bivoltine race of the silkworm Bombyx inori, but not (Wolsky, 1938) in pupae of Drosophila inclanogaster. Wolsky (1938) attributes this difference to the pupal stage being one of great activity as compared with diapause.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Bodine and Boell (1934) obtained CO-stimulation of respiration of diapause embryos of the grasshopper Mclanoplus differentialis and no significant effect of light. A similar stimulation by CO was found by Wolsky (1941) in a bivoltine race of the silkworm Bombyx inori, but not (Wolsky, 1938) in pupae of Drosophila inclanogaster. Wolsky (1938) attributes this difference to the pupal stage being one of great activity as compared with diapause.…”
Section: Discussionsupporting
confidence: 85%
“…A similar stimulation by CO was found by Wolsky (1941) in a bivoltine race of the silkworm Bombyx inori, but not (Wolsky, 1938) in pupae of Drosophila inclanogaster. Wolsky (1938) attributes this difference to the pupal stage being one of great activity as compared with diapause. Schneiderman and Williams (1954) found that the respiration of diapausing pupae of the Cecropia silkworm was but slightly affected by high concentrations of carbon monoxide ; further experiments (Harvey and Williams, 1958) demonstrated that a cytochrome system functioned in this material, the resistance to CO being accounted for by cytochrome oxiclase being present in great excess relative to cytochrome c.…”
Section: Discussionsupporting
confidence: 85%
“…It is also evident that the effects of submaximal cyanide concentrations depended upon the developmental stage of the pupae, for inhibition at a given concentration of cyanide decreased markedly in the later stages. Similar results were obtained by Wolsky (1938), with carbon monoxide and Drosophila pupae. In general terms, he proposed two explanations, namely ; " ( 1 ) there may be changes in the physical-chemical properties of the medium in which the Warburg-Keilin system is reacting, affecting the velocity constants of the reactions or the solubility of the gases; (2) there may be a qualitative change in the Warburg-Keilin system, which alters the velocity constants of its reactions, so that it reacts more readily with (X and less readily with CO." He also noted that the work of Szorenyi and Tschepinoga (1936), who reported that in trained muscles the oxygen consumption increased and at the same time the respiration became more resistant to cyanide.…”
Section: Inhibition By Cyanidesupporting
confidence: 87%
“…Agrell (1947) assumed that the U-shaped course of respiration is, to a certain degree, connected with variations in the activity of the dehydrogenase systems. Wolsky (1938) attributed the changes in oxygen consumption to the quantity or activity of the cytochrome system. The results of the present study support Wolsky's interpretation in part, but point also to additional complicating factors.…”
Section: Oxygen Consumptionmentioning
confidence: 99%
See 1 more Smart Citation